Bioinspired Core–Shell Nanoparticles for Hydrophobic Drug Delivery. (19th August 2019) - Yang, Guangze; Liu, Yun; Wang, Haofei; Wilson, Russell; Hui, Yue; Yu, Lei; Wibowo, David; Zhang, Cheng; Whittaker, Andrew K.; Middelberg, Anton P. J.; Zhao, Chun‐Xia
Abstract: A large range of nanoparticles have been developed to encapsulate hydrophobic drugs. However, drug loading is usually less than 10 % or even 1 %. Now, core–shell nanoparticles are fabricated having exceptionally high drug loading up to 65 % (drug weight/the total weight of drug‐loaded nanoparticles) and high encapsulation efficiencies (>99 %) based on modular biomolecule templating. Bifunctional amphiphilic peptides are designed to not only stabilize hydrophobic drug nanoparticles but also induce biosilicification at the nanodrug particle surface thus forming drug‐core silica–shell nanocomposites. This platform technology is highly versatile for encapsulating various hydrophobic cargos. Furthermore, the high drug loading nanoparticles lead to better in vitro cytotoxic effects and in vivo suppression of tumor growth, highlighting the significance of using high drug‐loading nanoparticles. Abstract : Kleintransporter auf der Nanoskala : Bifunktionale amphiphile Peptide wurden entwickelt, die sowohl hydrophobe Wirkstoffnanopartikel stabilisieren als auch Bio‐Verkieselung an der Partikeloberfläche verursachen können, wodurch die Langzeitstabilität erhalten bleibt. Die Wirkstoff‐Kern‐/Siliciumdioxid‐Schalen‐Nanokomposite zeigen eine außergewöhnlich hohe Wirkstoffbeladung (bis zu 65 % w/w) und Einkapselungseffizienz (>99 %).